Prevalence of anxiety, depression, and PTSD in exonerees: a brief report - Thomas, Kathryn A. (The journal of forensic psychiatry & psychology, 2023)
In the last three decades, there have been 3,248 documented wrongful convictions in the United States, with over 28,000 years served collectively by innocent defendants. Despite the high prevalence of wrongful convictions in the United States, there is a dearth of research examining the psychological impact of wrongful convictions. A total of 74 exonerees, the largest sample of exonerees to-date, completed an online survey designed to investigate the psychological experiences of people who were wrongfully convicted and subsequently exonerated. The study was designed with the goal of gaining a better understanding of the psychological experiences of people who are wrongfully convicted, including the prevalence of generalized anxiety disorder (GAD), major depressive disorder (MDD), and posttraumatic stress disorder (PTSD). Results revealed that exonerees face high rates of depression, anxiety, and PTSD. Specifically, exonerees reported four times higher rates of MDD, seven times higher rates of GAD, and 11 times higher rates of PTSD than the general population. Results from the current study reveal dire rates of mental health disorders in exonerees, suggesting a need for policy reform to improve access to mental health treatment for exonerees.